Teaching as Subversive Intimacy: Weaving Historical Thinking into Living Interpretive Narratives - Prakoso, Sugeng (Jurnal Pendidikan Sejarah, 2025)
This article proposes subversive intimacy—the deliberate pairing of trust and disruption—as a framework for reimagining history pedagogy in Indonesia. Based on a semester-long experiment in the undergraduate English as Historical Source course, it shows how structured scaffolding (such as writing guidelines and thematic workshops), followed by the strategic loosening of guidance, moved students from procedural compliance to interpretive freedom. Analysis of top student papers reveals how dialogical engagement, collaborative critique, and provisional authority fostered critical reading, nuanced argumentation, and intellectual risk-taking. Situated within debates on critical pedagogy and historical thinking, the study demonstrates the potential of this approach to unsettle didactic traditions and bring marginalized themes to the center of scholarly engagement—transforming the history classroom into a living arena for cultivating rigor, humility, and interpretive courage.